2018
DOI: 10.5830/cvja-2018-007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension as seen in a rural area in sub-Saharan Africa: high prevalence, late clinical presentation and a high short-term mortality rate during follow up

Abstract: PH, dominated by PHLHD, was common among adults attending this rural centre and was associated with a high mortality rate. Related co-morbidities and late clinical presentation reflect the poor socio-economic context. Improved awareness of PH among physicians could promote early diagnosis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…At six-month follow-up, 21% of adults with follow-up data had died [108]. Similar findings were seen in the Cameroonian study that screened 2194 patients via echocardiograms, and observed a crude prevalence of PH of 15.6%, with mortality during six months of follow-up of 28% [109].…”
Section: Pulmonary Hypertensionsupporting
confidence: 79%
See 1 more Smart Citation
“…At six-month follow-up, 21% of adults with follow-up data had died [108]. Similar findings were seen in the Cameroonian study that screened 2194 patients via echocardiograms, and observed a crude prevalence of PH of 15.6%, with mortality during six months of follow-up of 28% [109].…”
Section: Pulmonary Hypertensionsupporting
confidence: 79%
“…Pulmonary hypertension (PH) in SSA is associated with very high mortality [108,109]. Community-based prevalence data for PH are lacking in SSA.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Pulmonary hypertension due to left heart disease (LHD) under the 1998 classification was referred to as pulmonary venous hypertension and classified under Group II PAH 41 , 42 . Based on underlying etiology, Group II PH patients were generally classified under two main categories i.e., those with end-stage heart failure, or those with mitral valve disease.…”
Section: Risk Factors That Complicate Hiv-phmentioning
confidence: 99%
“…At least six reports have looked at the aetiology of pulmonary heart disease in SSA [190][191][192][193][194][195].…”
Section: Pulmonary Heart Disease (Cor Pulmonale) and Pulmonary Hypertmentioning
confidence: 99%